2015
DOI: 10.1002/ece3.1881
|View full text |Cite
|
Sign up to set email alerts
|

High richness of ectomycorrhizal fungi and low host specificity in a coastal sand dune ecosystem revealed by network analysis

Abstract: Ectomycorrhizal (EM) fungi are ubiquitous in temperate and boreal forests, comprising over 20,000 species forming root symbiotic associations with Pinaceae and woody angiosperms. As much as 100 different EM fungal species can coexist and interact with the same tree species, forming complex multispecies networks in soils. The degree of host specificity and structural properties of these interaction networks (e.g., nestedness and modularity) may influence plant and fungal community assembly and species coexisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
4
13
0
Order By: Relevance
“…Plant-ECM interactions are also believed to be conserved at the family level [55]. Analogous results have been noted in previous studies of ECM in native and exotic pines [8,10,24,26]. However, other studies have found that ECM host specialization contributes significantly to the composition of ECM communities [25,56].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Plant-ECM interactions are also believed to be conserved at the family level [55]. Analogous results have been noted in previous studies of ECM in native and exotic pines [8,10,24,26]. However, other studies have found that ECM host specialization contributes significantly to the composition of ECM communities [25,56].…”
Section: Discussionsupporting
confidence: 77%
“…Studies show that longer distances (>10 km) may limit the stochastic dispersal of fungal propagules from one location (native forest) to another (plantation) whereas deterministic traits such as dispersal via spores [14,18] versus mycorrhizal root tips and hyphal networks may operate at finer scales [19][20][21][22]. In addition, biotic (e.g., host nutrient demands, seed dispersal) and abiotic factors (e.g., soil chemistry) may facilitate ECM fungal species with physiological and ecological adaptations depending on the environmental context [23].Recent evidence has demonstrated that phylogenetic distance between exotic and native hosts might explain their (dis)similarities in ECM community composition and richness [24,25]. For example, studies have shown that co-occurring exotic pine and native trees host similar ECM fungal communities and share the same dominant ECM fungal species [8,10,[26][27][28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The color indicates functional groups. Genera > 1.00% are labelled Tomentella, and Geopora), which have also been confirmed previously by ECM ground surveys using molecular identification, at a global scale (Guo et al, 2020;Hayward, Horton, & Nunez, 2015;Long, Liu, Han, Wang, & Huang, 2016;Roy-Bolduc, Laliberte, & Hijri, 2016 (Nara, 2009;Peay, Schubert, Nguyen, & Bruns, 2012). Tomentella is an ECM fungi with saprotrophic ability, and identification using FUNGuild revealed that some symbiotroph fungi also exhibited free-living saprophytic life strategies.…”
Section: Predominance Of Ecm Fungi In Raf Communitiessupporting
confidence: 80%
“…There are two main reasons why we lack a mechanistic understanding of how belowground biodiversity changes during pedogenesis. First, studies of belowground biodiversity patterns with pedogenesis have mostly been conducted on a few individual soil chronosequences (13)(14)(15)(16)(17), with such work focusing mainly on a single group of belowground organisms, such as bacteria (16), fungi (18) or protists (19), or on changes in microbial biomass and community structure (17). Although such studies provide valuable information, pedogenesis often follows different trajectories depending on such factors as soil parent material and climate (7,8,(19)(20)(21).…”
Section: Significancementioning
confidence: 99%